Analisis Konstruksi Citra Maskulinitas pada Merek Perawatan Wajah Pria di Indonesia - Satrio, Sello; Pratama, Alfian; Handayani, Widhia Seni; Ghanistyana, Lathifa Prima; Nurapriyanti, Tia (Petanda: Jurnal Ilmu Komunikasi dan Humaniora, 2025)
The significant growth of the men's facial care market in Indonesia has triggered dynamic shifts that challenge the traditional hegemonic masculinity construction in the digital space. This study aims to deeply analyze how three prominent men's facial care brands (Kahf, MS Glow for Men, and Nivea Men) construct images of masculinity through their digital communication strategies, and to identify the patterns of meaning acceptance and negotiation by the audience. Employing a qualitative netnography approach, the core finding reveals that, instead of collapsing, hegemonic masculinity is locally negotiated, resulting in the conceptual model of Locally Negotiated Masculinity. This digital masculinity only accepts grooming practices through three strict justification mechanisms: Functional Justification (linking appearance as Professional Somatic Capital), Spiritual Justification (as Pious Consumption), and Non androgyny Boundary Negotiation which explicitly rejects the East Asian flower boy image. This model serves as a theoretical contribution to gender and digital communication studies in Southeast Asia, challenging Western metrosexual perspectives. The practical implication is that brands must integrate functional and spiritual narratives to legitimize the use of their products in this culturally sensitive market.